The geography of genetics: an analysis of referral patterns to a cancer genetics service - McDonald, Kevin; Iredale, Rachel; Higgs, Gary (Genomic medicine, 2007)
This study uses a geographical information system (GIS) and statistical analysis to look for patterns in referrals to a British cancer genetics service. In this case, familial cancers are taken to be those that can develop when an individual inherits DNA mutations that cause an increased risk of cancer. Between 1998 and 2006 the Cancer Genetics Service for Wales received nearly 11,000 referrals for patients resident in Wales and it is the service database recording those referrals which is the subject of this secondary analysis. Using postcodes to match referred patients to areas, deprivation scores were assigned. Referral rates per 10,000 head of population across the 8-year study period by unitary authority are presented, as is information on referrals from primary and secondary care sources by year. Each patient referred has their family history of cancer recorded and is assigned to a risk category; high, medium or average. There are correlations between number of GPs (General Practitioners) in a practice, number of patients referred from a practice, and deprivation as measured by the overall Welsh Index of Multiple Deprivation 2005, such that the two former factors increase as deprivation decreases. Over time there were changes in referral sources, with referrals from primary care overtaking those from secondary care in percentage and absolute terms. There were also changes in the types of cancer referred, risk categories seen and to which centre referrals were made. Referral patterns reveal an inverse relationship between deprivation and health service availability and use.